Pengaruh Corporate Social Responsibility (CSR) dan Kinerja Keuangan terhadap Nilai Perusahaan pada Perusahaan Perhotelan, Resort, dan Cruise Lines yang Terdaftar di BEI Tahun 2017-2022 - Pitri Zuhelmi; Jon Kenedi (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This research is motivated by the growth of the Hotel, Resort and Cruise Lines Industry which does not always increase every year. The value of the Hotel, Resort and Cruise Lines Industry shows a decline starting from 2017-2022. This increase and decrease in value can be changed by Corporate Social Responsibility (CSR) and Financial Performance. This research aims to: (1) Find out changes in Corporate Social Responsibility (CSR) towards Industrial Value, (2) Find out changes in Financial Performance towards Industrial Value, and to (3) Find out changes in Corporate Social Responsibility (CSR) and Financial Performance together. the same for the Industrial Value of the Hotel, Resort and Cruise Lines industry listed on the IDX in 2017-2022. The population in this study is the entire Hotel, Resort and Cruise Lines industry listed on the IDX in 2017-2022. Sample selection used purposive sampling technique. The number of samples obtained was 10 industries. The type of data collected is secondary data obtained from the IDX website. The analytical methods used are descriptive analysis, classical assumption test, multiple linear analysis, t test, f test, and analysis of the coefficient of determination (R2). The research results prove that: (1) Corporate Social Responsibility (CSR) has had a significant negative change in Industrial Value, (2) Financial Performance has had a significant positive change in Industrial Value, and (3) Corporate Social Responsibility (CSR) and Financial Performance have simultaneously had a significant change. on Industrial Value.